Understanding Pesticide Labeling - Rezazadeh, Amir (EDIS, 2020)
The pesticide label is more than just a piece of paper. It is a legal document recognized by courts of law. The pesticide label is your best guide to using pesticides safely and effectively. If a pesticide will be part of the pest management plan, understanding the content of the pesticide label is essential for using the pesticide safely and effectively. The information on the pesticide label is based on research, development and registration procedures that a pesticide must undergo before being used by a consumer.